Anti-Doping - Wintermantel J; Wachsmuth N; Schmidt W (Deutsche Zeitschrift für Sportmedizin)
Background: The World Anti-Doping Agency (WADA) did not publish the number of anti-doping rule violations (ADRVs) in sports before 2013, leading to a lack of information regarding ADRVs in certain countries and sporting disciplines. The present study aimed to provide an overview of the number and distribution of ADRVs among elite athletes of Olympic sports. Methods: A database of ADRVs was created for Olympic sports between 2000 and 2013based on an Internet search. The inclusion criterion was success of the athlete at the international level. The data were analyzed using descriptive statistics. Results: A total of 1,236 cases were found. The most frequent violations were the use of anabolic substances (>38%), followed by blood doping (15.3%) and stimulant use (14.2%). ADRVs were found in 120 countries; the countries that accounted for most cases were Russia (10.4%), the USA (6.8%), and Italy (4.9%). The most affected sports were track and field (29.4%), weightlifting (21.8%), and cycling (13.0%). Related to Olympic disciplines, however, weightlifting was by far in front. Numerous ADRVs were observed among Russian women athletes. The highest numbers of ADRVs in track and field were committed by athletes from Russia (n=53), the USA (n=37), and Jamaica (n=19). The prevalence of ADRVs among Russian track and field athletes was 4.1 times higher during Olympic versus non-Olympic years. Conclusion: Targeted and organized doping can be assumed to occur in certain disciplines and countries.Problemstellung: Bis zum Jahr 2013 wurde von der WADA die Anzahl der sanktionierten Dopingbefunde (anti-doping rule violations, ADRVs) nicht verffentlicht und es konnte somit keine Zuordnung zu bestimmten Lndern und hufig auch nicht zu bestimmten Sportarten erfolgen. Das Ziel der vorliegenden Studie war es, eine bersicht ber die Anzahl und Verteilung von ADRVs bei Weltklasse-Athleten in den olympischen Disziplinen zu erstellen.KEY WORDS: Anti-Doping Rule Violation, Olympic Disciplines, Athletics, Doping Prevalence, Russia